2008
DOI: 10.1159/000159121
|View full text |Cite
|
Sign up to set email alerts
|

Speech Performance and Sound Localization in a Complex Noisy Environment in Bilaterally Implanted Adult Patients

Abstract: Objective: To evaluate speech performance, in quiet and noise, and localization ability in adult patients who had undergone bilateral and simultaneous implantation. Study Design: Prospective multi-center study. Methods: Twenty-seven adult patients with profound or total hearing loss were bilaterally implanted in a single-stage procedure, and simultaneously activated (Med-El, Combi 40/40+). Subjects were assessed before implantation and at 3, 6 and 12 months after switch-on. Speech perception tests in monaural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 35 publications
7
105
2
Order By: Relevance
“…They showed that significant binaural benefits occurred only for the second group who had similar performance across ear. Similar results were reported in a study of Mosnier et al (2009) in which bilateral CI users were grouped as asymmetric (!20 percentage point difference in unilateral performance between ears; n ¼ 11) or symmetric (<20 percentage point difference between ears; n ¼ 16) performers. The authors found a significant binaural benefit for the symmetric subject group in quiet, but no significant binaural benefit for the asymmetric subject group.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…They showed that significant binaural benefits occurred only for the second group who had similar performance across ear. Similar results were reported in a study of Mosnier et al (2009) in which bilateral CI users were grouped as asymmetric (!20 percentage point difference in unilateral performance between ears; n ¼ 11) or symmetric (<20 percentage point difference between ears; n ¼ 16) performers. The authors found a significant binaural benefit for the symmetric subject group in quiet, but no significant binaural benefit for the asymmetric subject group.…”
Section: Introductionsupporting
confidence: 88%
“…The performance with these combinations never exceeded that with the unshifted bands alone in sentence and vowel recognition (particularly F1 information transmission) in quiet. In addition, bilateral CI users with asymmetric monaural speech scores in each ear (greater than 15 percentage points) show no binaural benefit, suggesting integration did not occur (Mosnier et al, 2009;.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations